2011
DOI: 10.1002/jmv.22242
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus gene expression and latent membrane protein 1 gene polymorphism in pediatric liver transplant recipients

Abstract: Immunosuppressed pediatric transplant recipients are at risk of developing Epstein-Barr virus (EBV)-associated complications (such as post-transplant lymphoproliferative disorders). Monitoring of the EBV DNA level in blood alone has a low predictive value for the post-transplant course of EBV infection and its complications. Therefore, additional prognostic markers are widely sought. The study aim was to analyze EBV gene expression patterns and LMP1 polymorphism in relation to EBV DNA levels in pediatric liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The 30-bp deleted LMP1 variant has been associated with lower EBV serum levels compared to wild-type LMP1 [92]. Other studies have revealed differences in signaling properties of LMP1 variants that influence B-cell survival and proliferation [93].…”
Section: Genetic Studies Gradually Unravel the Molecular Basis Of mentioning
confidence: 99%
“…The 30-bp deleted LMP1 variant has been associated with lower EBV serum levels compared to wild-type LMP1 [92]. Other studies have revealed differences in signaling properties of LMP1 variants that influence B-cell survival and proliferation [93].…”
Section: Genetic Studies Gradually Unravel the Molecular Basis Of mentioning
confidence: 99%
“…No consistent peripheral blood EBV gene expression patterns have been found that clearly associated with quantitative EBV DNA measurement 98,102 or are predictive for, or diagnostic of, PTLD although only small numbers of PTLD patients have been studied 54,97,99,102 . Currently there is no clear additional benefit of EBV gene expression profiling over measurement of EBV DNAemia alone in SOT recipients.…”
Section: Results/consensus Outcomesmentioning
confidence: 99%
“…45,54,99,102,103 Results have been variable, likely due to factors including nonstandardization of assays, use of pooled cells which precludes determination of specific expression patterns among individual cells, 6 populations studied 45,53,54,56,[97][98][99][100][101][102][103] and differences in study design. 53,54,[99][100][101][102] No consistent peripheral blood EBV gene expression patterns have been found that clearly associated with quantitative EBV DNA measurement 98,102 or are predictive for, or diagnostic of, PTLD although only small numbers of PTLD patients have been studied. 54,97,99,102 Currently there is no clear additional benefit of EBV gene expression profiling over measurement of EBV DNAemia alone in SOT recipients.…”
Section: Ebv Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations